Statistical Comparisons of Temperature Variance and Kinetic Energy in Global Ocean Models and Observations: Results From Mesoscale to Internal Wave Frequencies. Issue 5 (16th May 2020) - Luecke, Conrad A.; Arbic, Brian K.; Richman, James G.; Shriver, Jay F.; Alford, Matthew H.; Ansong, Joseph K.; Bassette, Steven L.; Buijsman, Maarten C.; Menemenlis, Dimitris; Scott, Robert B.; Timko, Patrick G.; Voet, Gunnar; et al.
Abstract: Temperature variance and kinetic energy (KE) from two global simulations of the HYbrid Coordinate Ocean Model (HYCOM; 1/12° and 1/25°) and three global simulations of the Massachusetts Institute of Technology general circulation model (MITgcm; 1/12°, 1/24°, and 1/48°), all of which are forced by atmospheric fields and the astronomical tidal potential, are compared with temperature variance and KE from a database of about 2, 000 moored historical observations (MHOs). The variances are computed across frequencies ranging from supertidal, dominated by the internal gravity wave continuum, to subtidal, dominated by currents and mesoscale eddies. The most important qualitative difference between HYCOM and MITgcm, and between simulations of different resolutions, is in the supertidal band, where the 1/48° MITgcm lies closest to observations. Across all frequency bands examined, the HYCOM simulations display higher spatial correlation with the MHO than do the MITgcm simulations. The supertidal, semidiurnal, and diurnal velocities in the HYCOM simulations also compare more closely with observations than do the MITgcm simulations in a number of specific continental margin/marginal sea regions. To complement the model‐MHO comparisons, this paper also compares the surface ocean geostrophic eddy KE in HYCOM, MITgcm, and a gridded satellite altimeter product. Consistent with the model‐MHO comparisons, the HYCOM simulations have a higher spatial correlation with the altimeter product than the MITgcm simulations do. On the other hand, the surface ocean geostrophic eddy KE is too large, relative to the altimeter product, in the HYCOM simulations. Key Points: Kinetic energy and temperature variance in global HYCOM and MITgcm simulations are compared with moored observations Model resolution has large impact on the supertidal internal gravity wave continuum band Spatial correlations with observations are higher in HYCOM than in MITgcm